Correlation Between ABO Blood Group and Activated Partial Thromboplastin Time (APTT) and Prothrombin Time (PT) Pathway Coagulation Parameters - Saputro, Tri Ade; Purwaningsih, Nur Vita; Maulidiyanti, Ellies Tunjung Sari (jitek, 2025)
Background: The ABO blood group is known to affect the levels of several coagulation factors, such as factor VIII and von Willebrand factor (vWF), which can affect the results of coagulation time. This study aims to analyze the relationship between ABO blood group and the coagulation parameters Activated Partial Thromboplastin Time (APTT) and Prothrombin Time (PT). Methods: This analytical cross-sectional study involved 45 healthy Medical Laboratory Technology students from Muhammadiyah University of Surabaya. Inclusion criteria were healthy volunteers; exclusion criteria included bleeding disorders, recent transfusion, smoking, or refusal to consent. Conducted in May 2025 at the Clinical Pathology Laboratory, data were analyzed using one-way ANOVA. Ethical approval was obtained from KEPK FIK Muhammadiyah University of Surabaya (No. 057/KEPK/F/V/FIK/2025). Results: The test results showed that the distribution of APTT and PT data was normal and homogeneous. There was a significant difference between blood groups on APTT values (p = 0.006), but there was no significant difference on PT values (p = 0.605). Blood type O has a higher APTT value than other blood types. Conclusion: There is a significant relationship between ABO blood group and APTT values, but not with PT. The difference in APTT values may be influenced by lower vWF and factor VIII levels in blood group O. This finding is important to consider in the interpretation of coagulation test results in clinical laboratories.